Corporate finance : theory & practice - Lumby, Steve; Jones, Chris M. (Andover : South-Western Cengage Learning, 2011)
Now in its eighth edition, this bestselling and highly-regarded textbook offers a complete introduction to financial management and corporate finance. Though it is predominantly theoretical in focus, "Corporate Finance: Theory and Practice" takes a relatively non-mathematical approach which offers textual explanations in a very accessible style. The authors' educational experience is apparent throughout the book: worked examples are given after each explanation and all chapters include summaries, quick questions and more detailed practice questions. It now includes Learning Objectives at the start of each chapter. It contains expanded coverage on risk and uncertainty in investment appraisal and the different techniques. It highlights numerical calculations/equations to make them stand out better. It features new, modern-looking text design.
Previous ed.: London: Thomson, 2003.
Includes bibliographical references and index.
oif 20/05/14
Loan
Keywords: Corporations; Business enterprises; Corporations; Business enterprises